GABA(B) receptors at glutamatergic synapses in the rat striatum. - Lacey, C; Boyes, J; Gerlach, O; Chen, L; Magill, P; Bolam, J (2005)
Although multiple effects of GABA(B) receptor activation on synaptic transmission in the striatum have been described, the precise locations of the receptors mediating these effects have not been determined. To address this issue, we carried out pre-embedding immunogold electron microscopy in the rat using antibodies against the GABA(B) receptor subunits, GABA(B1) and GABA(B2). In addition, to investigate the relationship between GABA(B) receptors and glutamatergic striatal afferents, we used antibodies against the vesicular glutamate transporters, vesicular glutamate transporter 1 and vesicular glutamate transporter 2, as markers for glutamatergic terminals. Immunolabeling for GABA(B1) and GABA(B2) was widely and similarly distributed in the striatum, with immunogold particles localized at both presynaptic and postsynaptic sites. The most commonly labeled structures were dendritic shafts and spines, as well as terminals forming asymmetric and symmetric synapses. In postsynaptic structures, the majority of labeling associated with the plasma membrane was localized at extrasynaptic sites, although immunogold particles were also found at the postsynaptic specialization of some symmetric, putative GABAergic synapses. Labeling in axon terminals was located within, or at the edge of, the presynaptic active zone, as well as at extrasynaptic sites. Double labeling for GABA(B) receptor subunits and vesicular glutamate transporters revealed that labeling for both GABA(B1) and GABA(B2) was localized on glutamatergic axon terminals that expressed either vesicular glutamate transporter 1 or vesicular glutamate transporter 2. The patterns of innervation of striatal neurons by the vesicular glutamate transporter 1- and vesicular glutamate transporter 2-positive terminals suggest that they are selective markers of corticostriatal and thalamostriatal afferents, respectively. These results thus provide evidence that presynaptic GABA(B) heteroreceptors are in a position to modulate the two major excitatory inputs to striatal spiny projection neurons arising in the cortex and thalamus. In addition, presynaptic GABA(B) autoreceptors are present on the terminals of spiny projection neurons and/or striatal GABAergic interneurons. Furthermore, the data indicate that GABA may also affect the excitability of striatal neurons via postsynaptic GABA(B) receptors.